Impact of Microfinance on Poverty Reduction: A Case Study of Khushhali Bank Mirpur Khas District - Lal , Shankar; Kumar , Dileep; Murtaza , Ghulam (Pakistan Journal of Humanities and Social Sciences, 2023)
Micro finance banks are an important tools to alleviate the poverty. They effectively helps the poor people by increasing their income level. The present study is designed to explore the impact of microfinance on poverty reduction in the Mirpurkhas district, using Khushhalibank as a case study. It examine the size of MF loan and effect of this loan on income level of beneficiaries. Analyzed the different variables like as size of loan, living standard and their impact on poverty rate. Sample of 300 respondent was taken randomly by using close ended questionnaire mainly focus on the customers of the Khushhalibank Mirpurkhas branch .Further raw data was analyzed with the help of SPSS 22.0 software and PLS . Finding concludes that microfinance is an effective tool for poverty alleviation, as it helps increase income and improve the living standards of the poor. Further suggests that microfinance institutions provide more effective opportunities for people living below the poverty line to invest money/capital based on their needs, experience, and knowledge. The study also suggests policy recommendations for planned improvements. The literature review highlights the importance of microfinance in poverty reduction, and how it has played a significant role in the economic development of people in rural areas. The study concludes that microfinance can be a powerful instrument in mitigating rural poverty.